Conditions : a feminist magazine of writing by women with an emphasis on writing by lesbians. (New York : Conditions, 1981)
Fonds Suzan Daniel (FSD)
Periodiciteit : viermaandelijks
Redactie : PO Box 56, Brunt Station, Brooklyn NY 11215
Frans
Periodiek